2020
DOI: 10.20944/preprints202005.0212.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

<strong>Selective Cytotoxic Effects of <em>Annona Squamosa Leaves </em>against Breast Cancer Cells via Apoptotic Signaling Proteins</strong>

Abstract: : Annona squamosa L. is an important medicinal plant used in traditional medicine for the treatment of various diseases. Different parts of A. squamosa L. have various therapeutic effects; however, the anticancer activity of the leaves has not yet been identified. In vitro, MTT, nuclear staining, and LDH assays were used to evaluate cell survival and proliferation in cells exposed to the extracts. The effect of the extracts on cell migration was investigated using a monolayer wound repair assay, and the apopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Leaves of Annona squamosa have a number of chemical compounds belonging to diverse groups, including phenolics, annonaceous acetogenins, saponins, flavonoids, alkaloids, glycosides, alkaloids, steroids, and terpenoids [ 62 ]. A study was conducted to investigate the in vivo and in vitro anti-breast cancer activity of ASL extracts [ 40 ]. Leaf extract at a concentration of 100 µg/mL exhibited strong cytotoxic and antiproliferative activities against breast cancer cell lines (MCF-7 and MDA-MB-231).…”
Section: Biological Activities Of Annona Squamosa L Leavesmentioning
confidence: 99%
“…Leaves of Annona squamosa have a number of chemical compounds belonging to diverse groups, including phenolics, annonaceous acetogenins, saponins, flavonoids, alkaloids, glycosides, alkaloids, steroids, and terpenoids [ 62 ]. A study was conducted to investigate the in vivo and in vitro anti-breast cancer activity of ASL extracts [ 40 ]. Leaf extract at a concentration of 100 µg/mL exhibited strong cytotoxic and antiproliferative activities against breast cancer cell lines (MCF-7 and MDA-MB-231).…”
Section: Biological Activities Of Annona Squamosa L Leavesmentioning
confidence: 99%
“…It has been reported that the A. squamosa leaf extract increased the expression of proliferative and apoptotic markers, which in turn enhanced the extract's anticancer effect on breast cancer cell lines. Additionally, they conducted an in vivo investigation, and it was found that the treatment of rats with the extracts had an impact on the tumor size, proliferative, and apoptotic indicators [16]. Furthermore, a previous study could be suggested that Graviola exerts its antitumor effect throughout the regulation of the tumor cell cycle as well as inducing apoptotic signals including an increase in antiapoptotic Bcl-2 gene expression [46].…”
Section: Discussionmentioning
confidence: 99%
“…both in vitro and in vivo [14]. Additionally, it was found that the treatment of rats with this fruit extract had an impact on the tumor size, proliferative, and apoptotic indicators [16]. The Annona muricata extract has selective inhibitory activity against cancer cells that was modulated by acerogenin activity in the complex I mitochondrial electron transport chain, hampering the process of ATP formation needed for cancer cell growth [17].…”
Section: Introductionmentioning
confidence: 99%
“…It can be seen from the structure-activity relationship (SAR) that A. squamosa and its biologically active compound have cytotoxic activity against several different cancer-causing cell lines [21]. In 2021, Acetogenins, Isoquinoline, Quercetin-3-O-glucoside, phenanthrene and annoreticuin were isolated from the three-fold antioxidant activity of A. squamosa having activity on breast cancer [22]. Considering all these promising results, several compounds have been isolated from commercially available quercetin 3 O glucoside.…”
Section: -9595mentioning
confidence: 99%